(untitled) - Hammond, Allen (Washington, 1998)
In Which World?, scientist Allen Hammond imaginatively probes the consequences of present social, economic, and environmental trends to construct three possible worlds that could await us in the twenty-first century: Market World, in which economic and human progress is driven by the liberating power of free markets and human initiative; Fortress World, in which unattended social and environmental problems diminish progress, dooming hundreds of millions of humans to lives of rising conflict and violence; and Transformed World, in which human ingenuity and compassion succeed in offering a better life, not just a wealthier one, and in seeking to extend those benefits to all of humanity.
Keywords: Economic forecasting,World politics; Forecasting; 1989-